2020
DOI: 10.1111/bjep.12382
|View full text |Cite
|
Sign up to set email alerts
|

The role of executive function in reading comprehension among beginning readers

Abstract: Empirical evidence supports the importance of executive function (EF) in reading, but the underlying mechanism through which EF contributes to the reading process is unclear. The present study examined the direct and indirect effects of EF on reading comprehension through the indirect pathway of language and cognitive skills (i.e., syntactic awareness and text‐connecting inferencing) among the beginning readers. The sample included one hundred and sixty‐five 2nd and 3rd grade students. The participants were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 70 publications
0
5
0
1
Order By: Relevance
“…The mediating role of higher-order cognitive skills may be explained by the possibility that L2 Chinese readers need to consume more cognitive resources during inference making and monitoring to comprehend Chinese sentences. Hung's (2021) recent study also found the intertwined relationship between syntactic skills and cognitive skills and found an indirect effect of executive function (as measured by working memory tasks and inhibition tasks) on Chinese Grade 2 and 3 students' reading comprehension through syntactic awareness (as measured by a word order correction task). It should be noticed that executive function covered some aspects of working memory and monitoring.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The mediating role of higher-order cognitive skills may be explained by the possibility that L2 Chinese readers need to consume more cognitive resources during inference making and monitoring to comprehend Chinese sentences. Hung's (2021) recent study also found the intertwined relationship between syntactic skills and cognitive skills and found an indirect effect of executive function (as measured by working memory tasks and inhibition tasks) on Chinese Grade 2 and 3 students' reading comprehension through syntactic awareness (as measured by a word order correction task). It should be noticed that executive function covered some aspects of working memory and monitoring.…”
Section: Discussionmentioning
confidence: 87%
“…However, whether syntactic knowledge may exert an impact on Chinese reading via cognitive skills has not been examined in depth. Hung’s (2021) recent study represents such an attempt to find the intertwined relationships between syntactic skills and cognitive skills. She found an indirect effect of executive function (as measured by working memory tasks and inhibition tasks) on Chinese Grade 2 and 3 students’ reading comprehension through syntactic awareness (as measured by a word order correction task).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Follmer (2018), using meta‐analysis approach, found that EF as an integrated mechanism moderately correlates with reading comprehension ( r = .36), irrespective of the age groups and the measures used to assess reading comprehension and EF. Nevertheless, in addition to the direct effect of EF on reading, more researchers became interested in the indirect effects of EF on reading comprehension in an attempt to address the question, “Why does EF support reading?” For example, there is recent empirical evidence supporting that EF is associated with different reading processing skills, such as syntactic awareness (Hung, 2021), reading fluency (Cirino et al, 2019), and visual skills (Liu et al, 2019). In this connection, Kim (2017) proposed a more comprehensive theoretical model, direct and indirect effects model of reading (DIER), which hypothesized EF as the ultimate contributor to various reading processes such as inferencing, parsing, and other high‐order reading processes (e.g., theory of mind) and explained through them how EF contributed to the reading comprehension performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Un ulteriore risultato mostra come le componenti esecutive di base, soprattutto le abilità di aggiornamento in memoria di lavoro, sono coinvolte in compiti di comprensione del testo sia nella modalità digitale che in quella cartacea. Il coinvolgimento delle FE in età scolare nella comprensione del testo cartaceo è un risultato consolidato da molti studi (Butterfuss e Kendeou 2018;Florit, Cain, e Mason 2020;Hung 2021), ma con il presente studio si dimostra che le FE sono coinvolte anche nella comprensione dei testi in modalità digitale.…”
Section: Risultatiunclassified